2000
DOI: 10.1083/jcb.150.2.293
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Signal–Induced Activation of Poly(Adp-Ribose) Polymerase

Abstract: We present the first evidence for a fast activation of the nuclear protein poly(ADP-ribose) polymerase (PARP) by signals evoked in the cell membrane, constituting a novel mode of signaling to the cell nucleus. PARP, an abundant, highly conserved, chromatin-bound protein found only in eukaryotes, exclusively catalyzes polyADP-ribosylation of DNA-binding proteins, thereby modulating their activity. Activation of PARP, reportedly induced by formation of DNA breaks, is involved in DNA transcription, replication, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(132 citation statements)
references
References 106 publications
(150 reference statements)
7
125
0
Order By: Relevance
“…In regard to what is known about the intracellular stimuli of PARP1, at least two signaling pathways, an increased intracellular Ca 2+ level and the activation of ERK1/2, have been found to activate PARP1 during hypertrophy [140,141]. By analysis of PARP-inhibitors, it was found that PARP activates the TEF1-mediated gene transcription from the M-CAT sites [136].…”
Section: Chromatin Modifying Enzymesmentioning
confidence: 99%
“…In regard to what is known about the intracellular stimuli of PARP1, at least two signaling pathways, an increased intracellular Ca 2+ level and the activation of ERK1/2, have been found to activate PARP1 during hypertrophy [140,141]. By analysis of PARP-inhibitors, it was found that PARP activates the TEF1-mediated gene transcription from the M-CAT sites [136].…”
Section: Chromatin Modifying Enzymesmentioning
confidence: 99%
“…Likewise, poly-ADP ribosylation is reversed by poly (ADPribose)glycohydrolase (Quenet et al, 2009). Interestingly, although poly-ADP ribosylation and PARP1 activity are most well known for their role in DNA repair following damage, PARP1 activation has been shown to increase in cortical neurons following depolarization (Homburg et al, 2000). Likewise, PARP1 is required for long-term synaptic facilitation and long-term memory in aplysia, suggesting a functional role in the nervous system (Cohen-Armon et al, 2004;Hernandez et al, 2009).…”
Section: Other Histone Modifications: Ubiquitination and Poly-adp Ribmentioning
confidence: 99%
“…Poly[ADP-ribose] polymerase 1 (PARP-1) is activated by stressful stimuli that damage DNA (Virág and Szabó , 2002), although it can also be induced by other physiological stimuli. Depolarization and exposure of cortical neurons to neuronal growth factor have been shown to activate PARP-1 in the absence of DNA damage (Homburg et al, 2000;Visochek et al, 2005). Moreover, it was shown recently that PARP-1 activation is required for long-term neuronal plasticity in Aplysia and mice (Cohen-Armon et al, 2004;Goldberg et al, 2009;Hernández et al, 2009).…”
Section: Introductionmentioning
confidence: 99%